WAQF FOREST AS A STRATEGY FOR REFORESTATION: A QUALITATIVE STUDY OF ECOLOGICAL SUSTAINABILITY IN ACEH - Fakhri, Ahmad Hazim; Abrar, Muhammad; Yusuf, Fakhri; Juli, Sabiruddin; Jamhuri, Jamhuri; Effendi, Erwan; Maisarah, Siti; Waeno, Mahamadaree (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Aceh has one of the largest forest areas in Sumatra. However, Aceh has lost approximately 117,000 hectares in the last 7 years. Although the Aceh government has addressed forest destruction through programs run by the environment and forestry agencies and regulatory support from Indonesian laws and Qanun, these measures have not been effective. In addressing this issue, Islam has a solution-oriented and relevant approach to tackling forest destruction through the concept of Waqf Forest. This study examined the implementation, positive impacts, and challenges, and will produce recommendations for the development of waqf forests in Aceh province. This study used a qualitative approach with a case study method to explore in depth the waqf forest model as a forest reforestation strategy in Aceh. Overall, this study highlights that the waqf forest model represents a promising strategy for addressing deforestation and supporting reforestation efforts in Aceh Province, while also identifying key challenges that hinder its optimal development. Contributing empirical insights into waqf forest implementation in Aceh, an area largely underexplored in prior literature. This research demonstrates that waqf forests hold significant potential as an Islamic philanthropic mechanism for advancing ecological sustainability and long-term forest conservation in the region.